GENDER DIVERSITY, STRUKTUR KEPEMILIKAN,DAN KINERJA PERUSAHAAN: STUDI PADA PERUSAHAAN PERBANKAN DI INDONESIA - Rani Raharjanti Raharjanti (Politeknik Negeri Semarang, 2019)
During emancipation era, women on board has been of major interest to corporate governance in recent years. The feminism already change the mindset of millenium people. This study analysis the affect of gender diversity, board size, bank size, ownership structure and capital structure on bank performance. By making use of cross sectional data for a sample of 28 conventional banks in Indonesia during period 2010-2017. Our empirical evidence shows that gender diversity (woman boardroom) has no effect to bank performance measured by Return on Equity. It is indicating that the executive has no effect to oversight the monitoring effect. It is reinforced by Bloomberg Businessweek’s research, woman on board in Indonesia in 2017 under 20 %. In addition, we found that there was a positive effect of bank size on bank perfomance. We also shows that findings of negative relationship between ownership structure and bank performance